A preliminary study on the online processing of anticipatory tonal coarticulation – Evidence from eye movements - Li, Qian (Frontiers in Psychology, 2023)
While the f0 realization of lexical tones vary extensively in contexts, little has been known on how listeners process the variation in lexical tones due to contextual effects such as tonal coarticulation in spoken word recognition. This study thus aims to fill the knowledge gap in tone perception with evidence from two types of anticipatory tonal coarticulation effects in Tianjin Mandarin, i.e., the slope raising effect due to a following low-falling tone and the overall-height raising effect due to a following low-dipping tone. An eye-tracking experiment with the Visual World Paradigm was carried out to compare participants’ eye movements when they heard targets in three types of anticipatory raising conditions, i.e., the Slope Raising condition, the Overall-height Raising condition, as well as the No Raising condition (the baseline). The eye movement results showed significant differences in the proportion of looks to target between the Slope Raising condition versus the other two conditions, whereas the Overall-height Raising condition did not differ significantly from the No Raising condition. The findings thus suggest the facilitatory effect of tonal coarticulation cues in the anticipation of the upcoming tones, but listeners in this study seemed to be only sensitive to the raising in the f0 slope rather than the overall raising in the f0 height.